Uji Antibakteri Isolat Endofit Asal Tanaman Kayu Jawa Lannea coromandelica (Houtt.) Merr. Terhadap MRSA Methicilin-Resistant Staphylococcus aureus - Eka Astuty; Maisya Zahra Al Banna; Astrid S. W. Sumah (Universitas Hasanuddin, 2020)
Asia is one of the regions with the highest incidence of Methicillin-resistant Staphylococcus aureus (MRSA) in the world. Endophytes in the tropics have not been widely studied and have not been explored, especially those related to their potential uses in medicine, agriculture, and other industries. Several research reports have also found that endophytic bacteria provide great potential in producing a variety of new natural products, including secondary metabolites that are similar to its host. This research is a true experimental laboratory to analyze the inhibition of endophytic bacterial isolates from kayu jawa (Lanneacoromandelica (Houtt) Merr on MRSA. The inhibitory test in this study uses the disc diffusion method. Antibacterial results The experimental results of the inhibitory test are expressed as the average ± standard deviation (SD) of two replications and the data is processed using Microsoft Excel 2007. Twelve endophytic bacterial isolates from kayu jawa have the ability to inhibit MRSA growth. visible from the formation of a clear zone around the paper disk.Based on the results of the measurement of the area of the clear zone formed, the twelve endophytic bacterial isolates are included in the strong category (11-20 mm) in inhibiting the growth of pathogens and of the twelve endophytic bacterial isolates, KJA3 isolates and KJB1 isolate which have ability inhibited the growth of MRSA best compared to other isolates because it has the largest inhibitory zone area of 17 mm and 16 mm.